Temperature dependency of energy shift of excitonic states in a donor–acceptor type TADF molecule - Youichi Tsuchiya; Keito Mizukoshi; Masaki Saigo; Tomohiro Ryu; Keiko Kusuhara; Kiyoshi Miyata; Ken Onda; Chihaya Adachi (Nature Communications)
Abstract In recent years, thermally activated delayed fluorescence (TADF) has attracted intense attention owing to its straightforward application to high-efficiency organic light-emitting diodes. Further, to develop high-performance TADF materials, many researchers have designed novel molecules that have a small energy gap between the lowest excited singlet and triplet states ( $$Δ E_{ST}$$ Δ E S T ), and detailed analysis suggests a significant contribution of higher-lying excited states for spin flipping processes. In this study, we demonstrate a peculiar thermal behaviour of emission decay of a donor–acceptor type TADF molecule, TMCz-BO, which seems like thermal deactivation of delayed fluorescence that can be explained without a negative $$Δ E_{ST}$$ Δ E S T by comprehensive kinetic analysis across various temperatures and solvents. While the activation energy has previously been treated as being temperature-independent, we stress that it should be a dynamic parameter affected by changing the solvent-solute interaction with the environmental temperature, especially in the case of a small energy gap.